Expression of CD1a, CD207, CD11b, CD11c, CD103, and HLA-DR receptors on the surface of dendritic cells in the skin of patients with atopic dermatitis - Ścibior, Kinga; Romańska-Gocka, Krystyna; Czajkowski, Rafał; Placek, Waldemar; Zegarska, Barbara (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2019)
Introduction : Atopic dermatitis (AD) is a chronic skin disorder of unknown etiopathogenesis. Its development is based on the influence of environmental factors, genetic and immunologic disorders. Undoubtedly, an important role is played by changes in quantitative and qualitative information on dendritic cells. Aim : Assessment of CD1a, CD207, CD11b, CD11c, CD103, and HLA-DR receptors on the surface of dendritic cells in the skin of patients with atopic dermatitis. Material and methods : The study group consisted of 45 patients with clinically diagnosed AD from whom biopsies were taken from the lesions. The control group was the material of 20 healthy people. To carry out the study the method of indirect immunofluorescence double staining reaction was used. Results : Studied receptors gave positive reactions in both groups. The number of cells in healthy individuals was significantly lower than in patients. They also differed in appearance and location of the skin. Conclusions : The CD1a/CD207 and CD1a/CD11c, CD1a/HLA-DR cell density was higher in AD patients compared to controls. There were differences in the location and appearance of the cells of AD patients compared to controls. All cells in the epidermis identified with antibodies CD1a, CD11c and CD207 were dendritic cells.